Is personal data protection a threat to access to information? A false normative antinomy, but a factual insecurity within Federal Institutions of Higher Education - Silva Neto, Carlos Eugênio da; Teixeira, Maria Luiza Firmino (My University, 2022)
This essay sought to analyze and understand the existence of any conflict between the Access to Information Law (LAI, Law no. 12,527/2011) and the General Personal Data Protection Law (LGDP, Law no. 13,709/2018), in public transparency within Federal Institutions of Higher Education (IFES). These legislative instruments comprise different disciplines—one focused primarily on public data and the other, on personal data, although they coincide as to the protection of personality rights. Its development was dri-ven by the following questions: is there an apparent conflict in the applicability of these legal contributions? Can the possible insecurity lead to a setback in public transparency? Data was collected by means of a ques-tionnaire applied to 22 federal universities and eight federal institutes, and then analyzed by a methodology combining field study with a qualitative analysis. First, the text presents the scope concerning the Access to Information Law as an instrument for effecting public transparency. Next, it discusses the guidelines of the General Personal Data Protection Law as a representative milestone in informational self-determination. Finally, the paper analyzes the reports on the difficulties faced by institutions in promoting compatibility between the LAI and the LGPD regarding the information requested to the Citizen Information Service.
Keywords: Comunicação Social; UNIDADE::SECRETARIA DE INTEGRIDADE PÚBLICA (SIP); Access to Information Law; General Personal Data Protection Law; Public transparency; ASSUNTO::Comunicação Social